The History of Ancient Greece and the Emergence of Medical Techniques in Greece - Intan Humairah; Intan Maulidya; Zunita; Said Muhammad Adiba; Muhammad Hafidz (Yayasan Yusda Edu Indonesia, 2026)
Ancient Greek civilization is one of the most important milestones in human history, laying the primary foundations for the development of Western science, philosophy, art, politics, and culture. This article aims to comprehensively examine the historical journey of Ancient Greece from the early Minoan and Mycenaean civilizations, through the development of the polis in the Archaic period, to the peak of its intellectual glory in the Classical period. The method used in writing this article is a literature study with a historical-descriptive approach, through the analysis of historical sources, scientific works, and relevant academic literature. The results of the study indicate that Ancient Greek civilization developed gradually through the interaction of geographical conditions, socio-political dynamics, and the development of rational thought that replaced mythological explanations. The legacy of Ancient Greece is visible not only in the form of physical remains such as buildings and works of art, but also in abstract concepts such as democracy, philosophy, and science, which remain influential to this day. This article concludes that Ancient Greece provided an important foundation for the formation of modern civilization, particularly in the context of rational thought and human values.